Sensory and phenolic profiling of Cyclopia species (Honeybush) and optimisation of the fermentation conditions - Theron, Karin Alicia (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc Food Sc)--Stellenbosch University, 2012.